Peningkatan Kapasitas Dalam Pemasaran Dan Promosi Pokdarwis Srikandi Kelurahan Tinjomoyo Semarang Melalui Bimbingan Teknis Manajemen Tata Kelola - Nungki Pradita; R Basiya; Artin Bayu Mukti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The role of Pokdarwis in carrying out the development of an area is considered strategic in building equal distribution of welfare for local communities. Pokdarwis Srikandi, which is based in the Tinjomoyo sub-district area of Semarang, is expected to be able to develop the potential of its area into tourism business activities that can revive the economy of the people in the area. With the average management and members having different educational backgrounds, the Pokdarwis management must work hard to continue to equip and improve the abilities of its members, especially in governance management. The form of Governance Management Technical Guidance activities includes lectures on Pokdarwis Governance, with material related to financial management, marketing and promotion of tourism products provided. Capacity and Capability Improvement Implementation of financial administration training is carried out by creating simple financial reports and directly practicing the process of recording the organization's income and expenditure transactions. Governance management capabilities are needed to realize sustainable tourism management in the Tinjomoyo Village area, especially in administrative and financial management